2011
DOI: 10.1016/j.jacc.2010.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Embolism Following Transcatheter Aortic Valve Implantation

Abstract: TAVI is associated with a high rate of silent cerebral ischemic lesions as evaluated by DW-MRI, with no differences between the TF and TA approaches. These results provide important novel insight into the mechanisms of CE associated with TAVI and support the need for further research to both reduce the incidence of CE during these procedures and better determine their clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
164
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(176 citation statements)
references
References 43 publications
11
164
0
1
Order By: Relevance
“…42 devices and approaches ( Figure 5). 35,[43][44][45][46][47] Analysis of diffusionweighted (DW) MRI studies performed pre-and post-TAVI includes a cumulative total of only 222 patients. TA-TAVI with ES was performed in 68 of these patients, with 52 (76.5%) having newly identified ischemic lesions on MRI postprocedure, and 2 (2.9%) with clinically manifest CVEs.…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…42 devices and approaches ( Figure 5). 35,[43][44][45][46][47] Analysis of diffusionweighted (DW) MRI studies performed pre-and post-TAVI includes a cumulative total of only 222 patients. TA-TAVI with ES was performed in 68 of these patients, with 52 (76.5%) having newly identified ischemic lesions on MRI postprocedure, and 2 (2.9%) with clinically manifest CVEs.…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%
“…43 Although early studies using DW-MRI supported this, 43,47 the association has not been confirmed by more recent studies. 35,[44][45][46] Similarly, although findings have been inconsistent, there is the suggestion of increased vulnerability of the anterior circulation in comparison with the posterior circulation, with a preponderance for new ischemic lesions in the middle cerebral artery territories. 35,44,45 Not surprisingly, the incidence and volume of preoperative silent ischemic lesions (present in 70% of patients) predicted the occurrence of new postoperative lesions.…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the average 30-day mortality in TAVR patients with post-procedural stroke was more than 3.5-fold higher than in non-stroke patients (25.5 vs. 6.9) [3]. In addition to the clinically apparent ischemic brain lesions, several cerebral magnetic resonance imaging studies have shown a very high (58-91 %) incidence of new ischemic lesions after TAVR, regardless of the transcatheter valve type and approach (Table 1) [4][5][6][7][8][9]. These small, usually asymptomatic, DWI lesions are most probably caused by micro-embolic particles arising during the valve implantation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Rodés-Cabau found no difference with cerebral MRI when transapical and transarterial approaches were compared. 4,8,12 However, 2 recent meta-analyses did suggest a lower stroke risk with transapical TAVI. Comparing transapical and transarterial access with the balloon expandable SAPIEN valve Eggebrecht found a neurological event rate (stroke/transient ischemic event) of 2.7% versus 4.2%.…”
mentioning
confidence: 99%